Photochemical Restoration of Light Sensitivity in the Degenerated Canine Retina - Sergei Nikonov; Natalia Dolgova; Raghavi Sudharsan; Ivan Tochitsky; Simone Iwabe; Jose-Manuel Guzman; Russell N. Van Gelder; Richard H. Kramer; Gustavo D. Aguirre; William A. Beltran (MDPI AG, 2022)
Photopharmacological compounds such as azobenzene-based photoswitches have been shown to control the conductivity of ionic channels in a light-dependent manner and are considered a potential strategy to restore vision in patients with end-stage photoreceptor degeneration. Here, we report the effects of DENAQ, a second-generation azobenzene-based photoswitch on retinal ganglion cells (RGC) in canine retinas using multi-electrode array (MEA) recordings (from nine degenerated and six WT retinas). DENAQ treatment conferred increased light sensitivity to RGCs in degenerated canine retinas. RGC light responses were observed in degenerated retinas following ex vivo application of 1 mM DENAQ (n = 6) or after in vivo DENAQ injection (n = 3, 150 μL, 3-10 mM) using 455 nm light at intensities as low as 0.2 mW/cm2. The number of light-sensitive cells and the per cell response amplitude increased with light intensity up to the maximum tested intensity of 85 mW/cm2. Application of DENAQ to degenerated retinas with partially preserved cone function caused appearance of DENAQ-driven responses both in cone-driven and previously non-responsive RGCs, and disappearance of cone-driven responses. Repeated stimulation slowed activation and accelerated recovery of the DENAQ-driven responses. The latter is likely responsible for the delayed appearance of a response to 4 Hz flicker stimulation. Limited aqueous solubility of DENAQ results in focal drug aggregates associated with ocular toxicity. While this limits the therapeutic potential of DENAQ, more potent third-generation photoswitches may be more promising, especially when delivered in a slow-release formulation that prevents drug aggregation.